PERLINDUNGAN HUKUM BAGI PEMEGANG POLIS ATAS PERUSAHAAN ASURANSI YANG DIPAILITKAN MENURUT UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG PADA PT. ASURANSI JIWA BUMI ASIH JAYA CABANG PEKANBARU - ASIKA EUNIKE SORMIN; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
PT Asuransi Jiwa Bumi Asih Jaya can be classified as an insurance company engaged in the field of life insurance, in this case the insurance products. A healthy insurance undertaking is an effort to address the risks faced by members of the public. Insurance companies that provide comfort for its customers, or the so-called policyholder also has shortcomings if they do not perform the payment of claims to policyholders.Company who can not make a payment due to the threat of bankruptcy, but if bankruptcy is not the case then they should have been paying claims and is responsible for customer risk. Results can be concluded that the authors obtained. The first protection obtained policyholder is not in accordance with provisions in the Act, second, that the responsibility of the insurance company does not fit because the insurance company can not give assurance and guarantee of payment of the claim.Keyword: Legal Protectio - Insurance - Bankruptcy